2009
DOI: 10.1126/scisignal.2000029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Intrinsic and TSC2-GAP–Regulated GTPase Activity of Rheb by Real-Time NMR

Abstract: Tuberous sclerosis complex 2 (TSC2), whose gene is frequently mutated in tuberous sclerosis, increases the guanosine triphosphatase (GTPase) activity of the small heterotrimeric GTP-binding protein (G protein) Rheb, thus resulting in the decreased activity of the mammalian target of rapamycin (mTOR), the master regulator of cell growth. Here, we describe the development of a nuclear magnetic resonance (NMR)-based, quantitative, real-time assay to explore the molecular mechanism of the intrinsic and TSC2-cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
89
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 71 publications
4
89
0
Order By: Relevance
“…We recently developed an NMR-based, real-time assay to measure the kinetics of GTP hydrolysis by the small GTPase Rheb by monitoring nucleotide-dependent changes in the NMR spectra of the GTPase protein (10). In this report, the NMR GTPase assay was extended to monitor intrinsic and PDZ-RhoGEF-mediated RhoA nucleotide exchange using native GDP and GTP as substrates.…”
mentioning
confidence: 99%
“…We recently developed an NMR-based, real-time assay to measure the kinetics of GTP hydrolysis by the small GTPase Rheb by monitoring nucleotide-dependent changes in the NMR spectra of the GTPase protein (10). In this report, the NMR GTPase assay was extended to monitor intrinsic and PDZ-RhoGEF-mediated RhoA nucleotide exchange using native GDP and GTP as substrates.…”
mentioning
confidence: 99%
“…S2b) (10). We have demonstrated that the real-time NMR methodology can be successfully used to assay nucleotide exchange in RhoA (11).…”
mentioning
confidence: 99%
“…The spectra were processed with NMRPipe (14), and the peak heights were analyzed with Sparky (15) via Gaussian line fitting. Residues from switches I and II, P-loop, ␤3 and ␤4, and the ␣3 helix that exhibit distinct well resolved peaks in each nucleotide-bound state were used as reporters of the reaction rates for each of the three GTPases, as described previously for Rheb (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations